2007
DOI: 10.1016/j.micres.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A marine killer yeast against the pathogenic yeast strain in crab (Portunus trituberculatus) and an optimization of the toxin production

Abstract: A pathogenic yeast strain WCY which could cause milky disease in Portunus trituberculatus was identified to be Metschnikowia bicuspidate according to the results of routine yeast identification and 18S rDNA and ITS sequences. After screening of more than 300 yeast strains from different sources in marine environments, it was found that strain YF07b had the highest ability to produce killer toxin against the pathogenic yeast. Strain YF07b was identified to be Pichia anomala according to the results of routine y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 9 publications
0
49
0
1
Order By: Relevance
“…Screening of killer toxin-producing yeasts was performed according to the methods described by Wang et al [14].…”
Section: Screening Of Killer Toxin-producing Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of killer toxin-producing yeasts was performed according to the methods described by Wang et al [14].…”
Section: Screening Of Killer Toxin-producing Yeastsmentioning
confidence: 99%
“…The results in Table 4 showed that C. tropicalis outnumbered other Candida species greatly and was considered to be a highly dominant species. It has been well documented that C. tropicalis could degrade different kinds of pollutants [14,16]. Other Candida spp.…”
Section: Isolation and Routine Identification Of The Yeast Strainsmentioning
confidence: 99%
“…Additional P. anomala killers include strains WC65, K36, YF07b and DBVPG3003 (Table 6.1; Sawant et al 1989;Guyard et al 1999;Comitini et al 2004;Wang et al 2007a). As for K5, the toxin of strain YF07b (isolated from marine environment for biocontrol of crab-pathogenic yeast species in the food industry) displays b-1,3-glucanase activity and has a similar molecular mass (47 kDa), raising the possibility that K5 and YF07b toxin are cognate proteins (Wang et al 2007a, b).…”
Section: B Pichiamentioning
confidence: 99%
“…In recent studies, it has been found that the yeast strains from marine environments can produce different extracellular enzymes for hydrolysis of different polymers [1][2][3][4][5][6]. Many enzymes such as amylase, inulinase, protease, b-1,3-glucanase (killer toxin) have been produced by different species of marine yeasts and their properties were characterized in this laboratory [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many enzymes such as amylase, inulinase, protease, b-1,3-glucanase (killer toxin) have been produced by different species of marine yeasts and their properties were characterized in this laboratory [1][2][3][4][5][6]. Among the enzymes, inulinase has received much attention as it can be widely applied to hydrolysis of inulin for production of fuel ethanol and high fructose syrup [3,7].…”
Section: Introductionmentioning
confidence: 99%